Decolorization of reactive azo dye by fenton and photo-fenton processes in aqueous solution: The influence of operating conditions, kinetics study, and performance comparison - Didar Değermenci, Gökçe (African Journals Online (AJOL), 2022)
ABSTRACT. In this study, the effect of Fenton and photo-Fenton processes, which are advanced oxidation processes that use the hydroxyl radical for the decolorization of Novacron Black from aqueous solutions, on decolorization was investigated. Optimum levels of initial pH, temperature, hydrogen peroxide concentration, initial dyestuff concentration, and iron concentration were determined. Initial pH, Fe2+ concentration, temperature, and initial Novacron Black concentration are the most effective experimental parameters in the decolorization of Novacron Black with Fenton and photo-Fenton processes. While the Novacron Black concentration was 200 mg/L, the H2O2 concentration was 100 mg/L, the initial solution pH was 3, and the temperature was 20 °C, a decolorization efficiency of 82.1% was obtained in the Fenton process at a concentration of 5 mg/L Fe2+, while in the photo-Fenton process at a 2 mg/L Fe2+ concentration, a 94.6% decolorization efficiency was obtained. Upon decolorization of Novacron Black, the photo-Fenton process had a higher removal efficiency than the Fenton process, even at low iron concentrations. From data obtained at various concentrations of initial Novacron Black, the non-linear method was used to determine the decolorization kinetics of Novacron Black. Finally, an economic analysis was carried out to compare the differences in operating costs between Fenton and photo-Fenton processes.

KEY WORDS: Advanced oxidation process, Decolorization, Fenton oxidation, Kinetic model, Photo-Fenton oxidation
Bull. Chem. Soc. Ethiop. 2023, 37(1), 197-210.
DOI: https://dx.doi.org/10.4314/bcse.v37i1.16
Keywords: Fenton oxidation; Decolorization; Photo-Fenton oxidation; Advanced oxidation process; Kinetic model